Rebooting India: realizing a billion aspirations - Nilekani, Nandan (Gurgaon, 2015)
ndia is sitting on a demographic dividend, expected to become the world?s youngest country by 2020, with 64 per cent of its population, roughly 800 million people, of working age. But our country cannot become a global powerhouse unless we resolve the contradictions and bridge the gaps that distort our society. According to Nandan Nilekani and Viral Shah, the only way to do this is by using technology to radically reimagine government itself. Rebooting India identifies a dozen initiatives where a series of citizen-friendly, high-tech public institutions can deliver low-cost solutions to India?s grand challenges. Based on the learnings from building Aadhaar, the proposed initiatives would save the government a minimum of Rs 1,00,000 crore annually, about 1 per cent of India?s GDP. These visionary, cutting-edge ideas, the authors hope, will enable each one of India?s 1.2 billion citizens to realize their aspirations.
Keywords: Developing India